Resistance training and sarcopenia - Francesco Giallauria; Antonio Cittadini; Neil Andrew Smart; Carlo Vigorito (Monaldi Archives for Chest Disease, 2016)
Aging is inexorably accompanied by a progressive decline of muscle mass, quality and strength. The resulting condition has been termed sarcopenia. Age-related sarcopenia can be accelerated by a variety of factors including changes in the hormonal milieu, inactivity, poor nutrition, chronic illness, and loss of integrity and function in the peripheral and central nervous systems. The downstream mechanisms by which these risk factors cause sarcopenia are not completely understood. Exercise training (particularly resistance training) has long been identified as the most promising method for increasing muscle mass and strength among older people. New interventions aimed at preventing muscle atrophy, promoting muscle growth and ultimately, maintaining muscle functions during aging are discussed. Understanding how age affects muscle-related gene expression, protein recycling and resynthesis, post-translational modification and turnover will be crucial to identify new treatment options.